All That Coughs Is Not COVID - Patel, Nisha M; Shaines, Matthew; Nori, Priya (Curēus (Palo Alto, CA), 2022)
We report the case of a woman from the Bronx, New York, who presented to the emergency department (ED) in June 2020 with a febrile respiratory illness resembling coronavirus disease 2019 (COVID-19) but was ultimately diagnosed with Legionnaires' disease (LD). New York City (NYC) rapidly became an epicenter of the global COVID-19 pandemic in 2020. In the years since the pandemic started, variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have recurred in multiple waves and remain an important cause of viral respiratory illness. The bacteria is often under-recognized as a cause of community-acquired pneumonia, yet it recurs each year in clusters, outbreaks, or as sporadic infections. Pneumonia caused by SARS-CoV-2 and can present similarly and may not be readily distinguished in the absence of diagnostic testing.